DESIGN OF THEMATIC INTEGRATIVE LEARNING BASED ON LOCAL ADVANTAGE IN ELEMENTRY SCHOOL - Sri Utaminingsih; Eka Zuliana (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2018)
The purpose of this research is to create the  integrated thematic learning design based on local advantage in Demak municipality for  3rd grade  with traditional game theme. The research design with first step: preparing for the experiment consist of :  : (1) literatur study anda FGD with teacher to identify core competences and local advantage, (2) designing the model with scientific approach: (observing, questioning, experimenting, associating, dan communicating), (3) planning for learning implementation, (4) planning for evaluation process by using authentics assesment and (5)Test showed an increase in the quality of the instructional design of learning; (6).  FGD with the expert to discuss early design so that can be get valid design. The result of this research can be get the design of model: integrated thematic learning based on local advantage in Demak municipalitythat can improve the quality of learning of elementary school students